2014
DOI: 10.1155/2014/615854
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration and Internal Models for Sensing Gravity Effects in Primates

Abstract: Gravity is crucial for spatial perception, postural equilibrium, and movement generation. The vestibular apparatus is the main sensory system involved in monitoring gravity. Hair cells in the vestibular maculae respond to gravitoinertial forces, but they cannot distinguish between linear accelerations and changes of head orientation relative to gravity. The brain deals with this sensory ambiguity (which can cause some lethal airplane accidents) by combining several cues with the otolith signals: angular veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…Although we make the argument that participants' behavior during a dynamic subjective vertical task can be explained simply by an increase in vestibular noise, it remains unclear how cerebellar degeneration might affect other gravity-related visual processing. Recent evidence suggests that along with the temporo-parietal junction (TPJ) [39], the cerebellum and vestibular nuclei also contribute to the process of predicting visually represented gravitational acceleration [40] (for a review, see [41]). If such processing occurs downstream of verticality estimation and relies on common models of gravity or such noisy vestibular cues, we might expect them to exhibit correlated deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Although we make the argument that participants' behavior during a dynamic subjective vertical task can be explained simply by an increase in vestibular noise, it remains unclear how cerebellar degeneration might affect other gravity-related visual processing. Recent evidence suggests that along with the temporo-parietal junction (TPJ) [39], the cerebellum and vestibular nuclei also contribute to the process of predicting visually represented gravitational acceleration [40] (for a review, see [41]). If such processing occurs downstream of verticality estimation and relies on common models of gravity or such noisy vestibular cues, we might expect them to exhibit correlated deficits.…”
Section: Discussionmentioning
confidence: 99%
“…5 Even if the theory of internal models does not focus comprehensively on modality-specific questions, internal models relyat least partially-on multimodal sensory streams and multisensory representations. [6][7][8] Extensive neurophysiological evidence on the integration of multisensory information down to the level of single neurons indicates a seamless integration of the senses, as well as a direct involvement of multisensory areas of the central nervous system (CNS) into motor regulation. [9][10][11][12] Even single multisensory convergence neurons in the deep layers of the superior colliculus integrate (afferent) visual, auditory, and proprioceptive input and affect orientation doi: 10.1111/nyas.13693 and attention behavior via (efferent) motor output, as described by Stein and Meredith 10 for cats.…”
Section: Introductionmentioning
confidence: 99%
“…Visual tasks have been shown to activate the insula. In an elegant study, Lacquaniti and colleagues, demonstrated that an internal representation of gravity is activated by visual motion that appears to be coherent with natural gravity (Indovina et al, 2005;Lacquaniti et al, 2014). The insular activation associated to neural predictive mechanisms was also observed during experiment of visual motion when comparing prediction versus perception of visual motion (Cheong et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The gravitational force significantly alters motion dynamics during the execution of movements. The insula, known to process the effects of gravity via a stored internal representation of gravitational acceleration, is activated for actual hand movements (Indovina et al, 2005;Lacquaniti et al, 2014;Rousseau et al, 2016). Here, we made a step forward by showing that the insula is also activated when the task mainly relied on mental predictive states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation